DESAIN PENGEMBANGAN MODEL PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN MELALUI ADDIE MODEL UNTUK MENINGKATKAN KARAKTER MAHASISWA DI UNIVERSITAS SLAMET RIYADI SURAKARTA - Trisiana, Anita; ., Wartoyo (PKn Progresif, 2016)
Citizenship Education in Higher Education is one of the compulsory subjects that make up the character of students. Long-term goals to be achieved in this study are as follows: find a design development Citizenship Through Education Learning Model to Improve Character ADDIE Students At University Slamet Riyadi Surakarta. The method used in this research is the research and development that is supported by the study of literature and literary documents and supported with Data Triangulation techniques appropriate to the problems discussed. Design development in this research using ADDIE (Analyze, Design, Develop, Implement, Evaluation). The results showed as follows: First Analysis is to analyze needs, identify problems (needs), and analysis tasks. Second, Design, this design phase, formulate learning objectives are SMART. Third, Development is the process of realizing blue-print. Fourth, Implementation is a concrete step to implement a learning system that we are creating. Fifth, Evaluation is the process to see if the system is being built successful learning, in line with initial expectations or not. Evaluation is the final step of the ADDIE model of instructional systems design. Based on the ADDIE model of instructional development was later adopted in the development stage learning model Project Citizen (PC) with a new name "MPC" (Modification of Project Citizen).